2011
DOI: 10.2215/cjn.04970610
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Creatinine Clearance from Modification of Diet in Renal Disease Study Equations in the ADEMEX Cohort

Abstract: SummaryBackground and objectives Twenty-four-hour urine and dialysate collections provide accepted means to assess adequacy in peritoneal dialysis (PD). Recent publications suggest that creatinine clearance (CrCl) estimated from the Modification of Diet in Renal Disease (MDRD) equations (eCrCl) accurately approximates measured CrCl (mCrCl) derived from 24-hour collections of urine and dialysate and might serve as an alternative means to assess small-solute clearance and adequacy in PD. Design, setting, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…A recent post hoc analysis of data from PD patients enrolled in ADEMEX study demonstrated that every 1 mL/ min/1.73 m 2 increase in estimated GFR by the four-variable MDRD equation was associated with a 6% increase in risk of death, but there was no association between measured Cr clearance and survival. This study also demonstrated a negative association between estimated GFR and Cr appearance rates [32]. Our results also suggest that muscle mass plays a predominant role in the serum Cr-mortality association in PD patients, supporting findings from earlier studies.…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 91%
See 2 more Smart Citations
“…A recent post hoc analysis of data from PD patients enrolled in ADEMEX study demonstrated that every 1 mL/ min/1.73 m 2 increase in estimated GFR by the four-variable MDRD equation was associated with a 6% increase in risk of death, but there was no association between measured Cr clearance and survival. This study also demonstrated a negative association between estimated GFR and Cr appearance rates [32]. Our results also suggest that muscle mass plays a predominant role in the serum Cr-mortality association in PD patients, supporting findings from earlier studies.…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 91%
“…In addition, some studies evaluating a survival benefit of early start of dialysis showed that a higher estimated GFR based on serum Cr level at dialysis initiation was associated with poorer survival, which could not be fully abolished by adjusting for known confounders such as age, sex, race, comorbidities, hemoglobin and serum albumin level [36][37][38]. This phenomenon is also likely to be caused by patients with a low muscle mass leading to a low plasma Cr and thus a high estimated GFR [32,39]. Our results showed that the association between higher serum Cr level with greater survival is still observed in a large PD cohort.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…As reported by the Modification of Diet in Renal Disease equations [4,5], more extensive and longterm studies will be needed to clarify eGFR, as proposed by JSN, as a new marker in the evaluation of PD dose and adequacy, because the simplicity of eGFR will be valuable in studies requiring huge sample sizes or the cooperation of multiple medical facilities.…”
mentioning
confidence: 99%